Emotional intelligence in the organizational behavior of manages - Natalia Vavdiiuk; Valentyna Galushchak; Іryna Abramova; Liudmyla Stryzheus (Економічний форум)
Emotional intelligence describes the ability to understand one's own feelings and the feelings of others, and how emotions can influence motivation and behavior in an organization. Emotional intelligence is important in leadership, in the leader's organizational behavior, it improves self-awareness, increases responsibility, promotes communication and the formation of trust in the team, helping leaders to perceive their emotions more positively, which allows them to solve problems more effectively and make decisions for managing the organization. Evaluation of the level of the managers emotional intelligence in the organization was carried out according to the methodology of D. Goleman's five competencies by management levels during January-February 2023. A practical self-report assessment of emotional intelligence was used for this study. The sample consisted of 30 people: 22 of them were male (73%) and 8 were female (27%). It has been established that top managers have high values of emotional intelligence – 17.086, middle managers – 16.86, first-line managers – 16.56. The hypothesis was formed and proved: with the growth of emotional intelligence of managers of higher management levels, the emotional intelligence of managers of lower management levels will also grow and vice versa. The relationship between the number of managers at each level of management and their levels of emotional intelligence is very high: as the emotional intelligence of managers at the highest level of management decreases, so will the emotional intelligence of managers at lower levels of management. The statistical significance of the hypothesis was checked by the coefficient of determination and Fisher's and Student's criteria